Effective use of flashcards as a teaching-learning methodology in the orthodontic laboratory discipline (Research, Society and Development, 2022)
Of the different branches of Dentistry, one of the studies of complex learning is Orthodontics. Seeking the opportunity for reinforcement - more easily, it was used in monitoring, a pedagogical support service, which offers a service for the development of technical skills and theoretical deepening, using a teaching and learning strategy using flashcards that launch the active recording principles and spaced repetition. The aim is to evaluate the flashcard learning method as learning and learning during the COVID-19 pandemic period. This is a descriptive, cross-sectional and qualitative-quantitative study, whose sample consisted of 42 students enrolled in the orthodontics laboratory discipline, who used a flashcard tool and who voluntarily responded to the individual online collection instrument. The absolute data for export to the stratified value from alpha C (SP) to the stratified value. It was observed that 61.9% of the students studied a teaching-learning tool, 64.3% indicated that a tool contributed to an excellent contribution of knowledge in an excellent way through a tool in the process of excellent knowledge of the discipline. The flashcard evaluation showed excellent internal consistency (α = 0.806). Flashcards have proven to be a useful resource for learning, especially in the long term, being a technology that can be shared among a group of students or even in a digital application.